2015
DOI: 10.2527/jas.2015-9509
|View full text |Cite
|
Sign up to set email alerts
|

A cooperative study on the standardized total-tract digestible phosphorus requirement of twenty-kilogram pigs1

Abstract: A cooperative study comprising growth performance, bone mineralization, and nutrient balance experiments was conducted at 11 stations to determine the standardized total-tract digestible (STTD) P requirement of 20-kg pigs using broken-line regression analysis. Monocalcium phosphate and limestone were added to a corn-soybean meal-based diet at the expense of cornstarch to establish 6 concentrations of STTD P from 1.54 to 5.15 g/kg in increments of 0.62 g/kg at a constant Ca:total P of 1.52:1.0. Diets were fed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…Predicted daily protein retention remained largely constant across all STTD P feed content. While daily protein retention predictions for the pig genotypes of Ekpe et al (76) and Pomar et al (77) were very close to the reported mean values, the simulated daily protein retention for the pig genotypes of Adeola et al (78) was systematically lower than the mean values ( Figs. 8 and 9).…”
Section: Model Validationsupporting
confidence: 62%
See 4 more Smart Citations
“…Predicted daily protein retention remained largely constant across all STTD P feed content. While daily protein retention predictions for the pig genotypes of Ekpe et al (76) and Pomar et al (77) were very close to the reported mean values, the simulated daily protein retention for the pig genotypes of Adeola et al (78) was systematically lower than the mean values ( Figs. 8 and 9).…”
Section: Model Validationsupporting
confidence: 62%
“…As a result, these predictions are to some degree linked to these parameter estimates and hence are not fully independent of the observations used for their validation. Predictions of ADFI were more accurate than those of protein and P retentions (mean absolute percentage errors of 2•47 v. 5•95 and 15•7 %, respectively) and could be attributed to challenges in the estimation of digestibility and efficiency of utilisation for protein and P. There was no systematic error in the predictions of P retention, ADFI, but protein retention was consistently underestimated for one study (78) . Potential reasons for this underestimation could be due to inaccuracies in the estimated pig phenotype parameters or in the reported feed composition, which were used as a model input, or could be due to the aforementioned uncertainties concerning the digestibility and efficiency of utilisation values for protein and P.…”
Section: Model Results and Validationmentioning
confidence: 87%
See 3 more Smart Citations